The Call of Cthulhu and Other Weird Stories - Lovecraft, H. P. (London Penguin Classics, 2002)
Collecting uniquely uncanny tales from the master of American horror, H.P. Lovecraft's The Call of Cthulhu and Other Weird Stories is edited with an introduction and notes by S.T. Joshi in Penguin Modern Classics. Credited with inventing the modern horror tradition, H.P. Lovecraft remade the genre in the early twentieth century. Discarding ghosts and witches, and instead envisaging mankind at the mercy of a chaotic and malevolent universe, Lovecraft's unique works would prove to be a huge influence on modern horror writers such as Stephen King. This selection of short stories ranges from early tales of nightmares and insanity such as 'The Outsider' and 'The Rats in the Walls' through the grotesquely comic 'Herbert West - Reanimator' and 'The Hound', to the extraterrestrial terror of 'The Call of Cthulhu', which fuses traditional supernaturalism with science fiction. Including the definitive corrected texts, this collection reveals the development of Lovecraft's mesmerising narrative style and establishes him as a hugely influential - and visionary - American writer. Howard Phillips Lovecraft (1890-1937), born in Providence, Rhode Island was self-educated and lived in his birthplace all his life, working as a freelance writer, journalist, and ghostwriter. Using many pen names, he contributed his supernatural/horror and science fiction/fantasy stories to various pulp magazines but his reputation as a writer rests mainly on the 60 or so stories he published in the pulp magazine Weird Tales starting in 1923.